PENGARUH FASILITAS, GAJI DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Jeby Dimas Prabowo; Bayu Pramutoko (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Company must be able to strive for anything that can increase the productivity of its employees in meeting the company itself, one alternative is to provide incentives. Work productivity is the ability to produce goods and services from various resources or production factors that are used to increase the quality and quantity of work produced in a company. The variables in this research are Facilities (X1), Salary (X2) Incentives (X3) and Employee Productivity (Y). The number of samples in this study were as many as 80 people who were obtained from all employees of UD. Karya Abadi Kediri. The technique used in this sampling is saturated sampling. To process the data in this study using the validity test, reliability test, double linear regression test which includes t test and f test. The results obtained in this study indicate that the Facility, Salary, and Incentive variables have positive and significant results on the Employee Productivity variable. From the results of the t test, it is stated that the facility variable has a value of 0.000, which is less than 0.05, it can be stated that the facility variable has a positive and significant impact on employee productivity. The salary variable has a result of 0.000, where the result is less than 0.05, it is considered positive and significant. The incentive variable has a result of 0.022, where the result is less than 0.05, it is considered positive and significant. The results of the F test calculation show that the F count is 38,470 with a sig. F (0.000) <0.05, thus facilities, salaries, and incentives simultaneously influence employee productivity variables.